SOCIO-PSYCHOLOGICAL FACTORS OF PEDAGOGICAL AUTHORITY AND RESPECTABILITY FORMATION - Vazieva, Alfiya; Chirkova, Svetlana; Galiev , Rustem; Gayfutdinova, Tatyana (Revista Inclusiones, 2020)
Organization of management and leadership both in small and large groups of people within any social environment and under all psychological conditions is associated with the phenomena of authority and respectability. In this work we will focus on the relationship between the teacher’s authority and group parameters. Does authority affect training and education, social and psychological processes in an academic group? Taking into account some theoretical assumptions, we can suppose that this effect is rather complex and mediated than direct. In the process of educating a teacher’s authority most likely affects students’ motivation for learning, their diligence, discipline and attention, as well as increases their interest in the subject and then through these intermediate links the teacher’s authority affects the learning outcomes.